Trends in elevated waist-to-height ratio and waist circumference in U.S. adults and their associations with cardiometabolic diseases and cancer, 1999–2018 - Yang, Bo; Yang, Jingli; Wong, Martin Ming-him; Rana, Juwel; Yang, Qinghua; Chan, Vicky; Khan, Moyukh Shabon; Yang, Aimin; Lo, Kenneth (Frontiers in Nutrition, 2023)
Although waist-to-height ratio (WHtR) has established association with cardiometabolic disease, the trend of changes in elevated WHtR among general population have not been examined adequately. This study examined the prevalence of elevated WHtR and waist circumference (WC) and their trends over time using Joinpoint regression models among adults who participated in the United States National Health and Nutrition Examination Survey (U.S. NHANES) 1999-2018. We performed weighted logistic regression to identify the association between central obesity subtypes and the prevalence of comorbidities, including diabetes, chronic kidney disease, hypertension, cardiovascular disease, and cancer. The prevalence of elevated WHtR has increased from 74.8% in 1999-2000 to 82.7% in 2017-2018 while elevated WC also increased from 46.9% in 1999-2000 to 60.3% in 2017-2018. Men, older adults, former smokers, and people with lower education levels were more likely to have elevated WHtR. A total of 25.5% of American adults had normal WC but elevated WHtR, and they had a significantly higher chance of suffering from diabetes (odds ratio [OR]= 2.06 [1.66, 2.55]), hypertension (OR= 1.75 [1.58, 1.93]) and CVD (OR= 1.32 [1.11, 1.57]). In conclusion, the burden of elevated WHtR and WC have been increasing among U.S. adults throughout the years, and the changes have been more significant across most subgroups. It is also notable that approximately a quarter of the population had normal WC but elevated WHtR, which had increased likelihood of having cardiometabolic diseases, especially diabetes. Future clinical practices should pay more attention to this subgroup of the population with overlooked health risks.